STRATEGI PEMBELAJARAN PAI EFEKTIF - Mariam Mariam (BRIGHT VISION Journal of Language and Education, 2022)
This study aims to describe Effective PAI learning strategies. This research uses the literature study method. The results of this study show that in general the types of Islamic Religious Education learning strategies in general are Expository Learning, Inquiry Learning Strategies and Cooperative Learning Strategies. In the learning process, a teacher as a teacher must be clever in taking steps so that the learning process can be carried out properly and achieve educational goals. Among them is to choose the right learning strategy. There are several things to consider and consider in choosing a PAI learning strategy.Keywords: Strategy, Learning, PAI